A return to innate arbitration culture: implications from a cost and efficiency perspective. (16th April 2019) - Baykitch, Alex; Bao, Edmund
Abstract: In the past decade, one consistent criticism has been the perception of increased cost and time penalties associated with the arbitral method. The authors suggest that the root of the problem lies in a failure to view international arbitration as an outcome-based mechanism instead of a procedurally driven process. The authors challenge current methods of procedural harmonization aimed at addressing the issue, which are premised upon the existence of a universally coherent and explicit arbitration culture in practice. Instead, they argue what is required is a return to an innate arbitration culture, defined as the recognition of international arbitration as a dispute resolution mechanism fundamentally separate to and distinct from domestic litigation. To that end, the authors advocate a return to innate arbitration culture, premised upon leveraging arbitration specific values of contractual flexibility, arbitrator discretion, institutional innovation and party autonomy. Only then can the cost-efficiency issue be addressed in a uniformly consistent way and the dissonance in user experience be reconciled with the discrepancy in user results.